Large-scale Patterning of Hydrophobic Silicon Nanostructure Arrays Fabricated by Dual Lithography and Deep Reactive Ion Etching - Ma, Zhibo; Jiang, Chengyu; Yuan, Weizheng; He, Yang (Nano-Micro Letters, 2013)
We describe a simple but efficient technique to fabricate large-scale arrays of highly ordered silicon nanostructures. By coupling dual lithography using light of 351.1 nm wavelength with deep reactive ion etching (DRIE), silicon nanostructures of excellent regularity and uniform coverage were achieved. The proposed nanofabrication method not only simplified the nanofabrication process but also produced high-aspect-ratio (higher than 15) nanostructures. The scalloping problem was also controlled by regulating DRIE parameters. The process is rapid, cheap, examined to optimize the fabrication process, and has the potential to be scaled up to large areas. The contact angle of a water droplet atop the surface is larger than 15°. Moreover, by coupling black silicon process with DRIE-based microfabrication, three-dimensional nano/nano dual-scale structures which show robust and stable hydrophobicity have been achieved. This process opens new application possibilities in optical, photoelectric, microelectronic, catalytic and biomedical applications.